Admission and Clinical Documentation Services (SADC): documentary physician at the service of health - Ramos Martín-Vegue, Arturo J. (Informação em Pauta, 2021)
The Admission and Clinical Documentation Services (SADC) were born in the Spanish hospitals of the National Health Service in 1989, with the aim of standardizing and unifying the functions that were developed in the Admission Units and in the Documentation and Archive Services. The legislative basis of this Service, its organization chart, the professional profile of the doctors, their competencies and the contribution of the SADC of the Puerta de Hierro Majadahonda University Hospital (Madrid) in achieving the 500 seal of the European Foundation for Quality Management (EFQM)